Exercise-Based Interventions in Hemodialysis Patients: A Systematic Review with a Meta-Analysis of Randomized Controlled Trials - Bogataj, Špela (J Clin Med, 2019)
There is a lack of agreement on the efficacy of different exercise interventions in hemodialysis patients. We analyzed which exercise type is the most beneficial in terms of functional fitness and inflammation. A literature search of seven databases yielded 33 studies that met the inclusion criteria. Compared with an inactive control, the intervention group showed moderate effects (ES = 0.74; 95% CI 0.35 to 1.14; p < 0.001; and ES = 0.70; 95% CI 0.39 to 1.01; p < 0.001; respectively) on functional capacity (six-minute walk test) and oxygen consumption. Small nonsignificant effects were observed for aerobic (ES = −0.36; 95% CI −0.85 to 0.13; p = 0.154) and resistance (ES = −0.44; 95% CI −1.07 to 0.19; p = 0.169) training types, whereas moderate effects were found for combined (ES = −0.69; 95% CI −1.47 to 0.10; p = 0.088) training type based on a 10-repetition sit-to-stand test. Further, large and small effects were observed for aerobic (ES = −1.21; 95% CI −1.94 to −0.49; p = 0.001) and resistance training (ES = −0.54; 95% CI −0.90 to −0.17; p = 0.004) types on C-reactive protein. Overall, the results showed the numerically largest effect sizes for combined types compared to solely aerobic or resistance training types, with the differences between training types not reaching statistical significance. There was a significant modifying impact of age, training frequency, and session duration on performance and inflammatory outcomes.